Analysis of Direct Financing Planning in Improving the Quality of Learning at An Nasiriin Islamic Middle School - H. Soro , Suharyanto; Sirotjuddin, M.; Mustofa, Mustofa (Global Education Journal, 2025)
The quality of learning is an important indicator in assessing the success of the education system. Quality is also greatly influenced by the effectiveness of financing planning. This study aims to analyze direct financing planning in improving the quality of learning at SMP Islam An Nasiriin using GR Terry's management theory, which includes the functions of planning, organizing, implementing, and supervising. This study uses a case study approach, with data collection methods through observation, interviews, and documentation studies. The results of the study indicate that SMP Islam Nasiriin has carried out financing planning correctly. Planning is based on learning needs; organizing is done through a clear division of tasks; implementation is directed at quality improvement activities; and supervision includes financial evaluation and student learning outcomes. Despite challenges such as limited teacher financial literacy and minimal digitalization, the school is able to respond adaptively through internal training and managerial innovation. In conclusion, direct financing planning with the right managerial approach contributes positively to improving the quality of learning, and can be a model for other educational units in results-based education financing planning.